High-pressure phase equilibrium calculations for carbon dioxide + cyclopentane binary system - Sima, Sergiu (2014)
The phase behavior of the carbon dioxide + cycloalkane mixtures usually receives low attention, though these systems are important for many industries, e.g. the carbon capture and storage. In this paper calculations results for the carbon dioxide + cyclopentane binary system are presented, based on SRK and PR cubic equations of state with classical van der Waals mixing rules. A single set of binary parameters for each model was proposed to predict the global phase behavior of the system in a wide range of pressure and temperature. Albeit the thermodynamic models used are simple, they are able to represent fairly well the phase behavior of the system analyzed in this paper.